Dynamic Programming Models of Fishing: Competition. - Levhari, David; Michener, Ron; Mirman, Leonard J. (American Economic Review)
This article focuses on the study regarding the case of free-entry competition. It is natural to consider the stock of any renewable resource as a capital stock and treat the exploitation of that resource in much the same way as one would treat accumulation of a capital stock. Three issues which have been raised only tangentially are important for the understanding of the economics of renewable resources. The first section analyzes the time path of prices, output, and resource stock under the assumption of free-entry competition, and the second section studies optimal planning.